Koloman dan Transformasi Nilai Persaudaraan dalam Merajut Kerukunan Bermasyarakat (Studi Koloman di Dusun Sumberjati Laok Bungbaruh Kadur Pamekasan) - Ridho, Ali; Suharyanto, Ernaka Heri Putra (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Harmony in society is the main capital for upholding the unity and integrity of the nation, when many parties make efforts to undermine unity and integrity in various ways ranging from spreading hoax news, inciting, takfiri, etc., then the column that became the routine of rural communities became the solution to this very worrying condition. This study aims to 1) describe the column model that transforms into community harmony. 2) reveal the steps taken by the community in maximizing the role of the columnist, and 3) reveal the impact of the implementation of the column on community harmony as an offer of the concept of world community harmony through small steps for a very big goal. This research uses a descriptive qualitative research method with a case study type, data collected through interviews, observations, and documentation notes. Data analysis used the Spradley Analysis Model with data collection, reduction, presentation, and conclusion drawing. From the research conducted, the conclusions are as follows 1). In the Monday night column in Sumber Jati Bungbaruh Hamlet, Kadur Pamekasan carries the concept of togetherness and concern for others. 2) column members eliminate egocentricity for the sake of the greater interest, in addition to carrying out religious activities (tahlilan and shalawatan) as well as solving social problems, and 3) impact the most real thing is harmony and religious people because it eliminates egocentricity for the sake of togetherness, security, and comfort.